Leadership Management and Organizational Governance Training for the Head of the National Madani Capital Customer Group, Badar Unit, Southeast Aceh Regency - Zulyadin Brutu; Farma Andiansyah; Dicky Zulkarnaen (Journal of Community Service and Rural Development, 2025)
This community service activity aims to improve the leadership capacity and organizational governance of the group leaders of Permodalan Nasional Madani (PNM) Badar Unit customers in Southeast Aceh Regency. The background of this activity is the low understanding and managerial skills of group leaders in managing internal group dynamics, which has an impact on the effectiveness of the community economic empowerment program. The implementation method uses a community-based learning approach combined with experiential learning through preparation stages, two-day core training, and evaluation. Training materials include participatory leadership, organizational communication, conflict management, and community-based group governance. The results of the activity showed a significant increase in the cognitive and skill aspects of the participants, as evidenced by an average increase in the post-test score of 36% compared to the pre-test. In addition, participants showed high enthusiasm and commitment to implementing the practices learned in their respective groups. In conclusion, this training is effective in improving local leadership capacity and contributing positively to the sustainability of the PNM empowerment program. Follow-up in the form of routine assistance is needed so that the impact of the training is long-term and sustainable